ANTHROPOMETRIC STUDY OF LEFT EXTERNAL EAR: A CROSS-SECTIONAL STUDY IN MEDICAL STUDENTS OF UDAIPUR, RAJASTHAN - SHRIVASTAVA, BHAVANA; ACHARYA, SUNITA; BHARAMBE, VAISHALY KISHORE; MEDATWAL, BHUPESH (International Journal of Current Pharmaceutical Research, 2024)
Objective: The human ears are specific to an individual because the auricle is also a distinctive feature of a person like other identification features so it is used in various areas of science like forensic medicine, anthropology, and biology. The ear lobule is the last part of the auricle to develop. Methods: This study was carried out among 100 students (50 Male and 50 Female) with age range from 18 to 25 years. The study was conducted in the Department of Anatomy, Pacific Institute of Medical Sciences, Udaipur, Rajasthan, India. Results: Total ear length and ear width were significantly higher in male than female (p value<0.0001) in this study. Lobule length and lobule width of left ear were compared by independent t-test, it was found nonsignificant (p value 0.5706) and significantly higher in male than female (p 0.0017) respectively. The mean value of lobule index of left ear was found significant with higher value in male while the mean value of ear index of left ear was found nonsignificant. Conclusion: Results according to genders who participated in the study where all dimensions (total ear length, ear width, lobule width and lobule index) were higher in male as compared to the female subjects. Although there was no significant difference observed in lobule length and ear index of left ear of male and female subjects.